Realising student voice through dialogic engagement with a microblogging tool. Issue 1 (2nd January 2023) - Cook, V.; Warwick, P.
ABSTRACT: The realisation of voice is a particularly challenging aspect of dialogue. The aim of this study is to explore how a microblogging tool creates conditions for the realisation of student voice. Drawing on data collected as part of a larger international study, analysis of student focus group interviews (aged 11–12 years) in two schools in England (n = 36) suggest that the use of a microblogging tool can develop student agency, helping to realise student voice by removing the struggle to capture and maintain the floor and enabling students to become attuned to the ideas of others. However, some students were concerned about the tool's democratic use. Guided by this finding, a detailed micro-analysis of interactions of video data, lesson transcripts and microblog meta-data explores how students' microblogging contributions were heeded by three teachers in one school. We consider the pedagogical implications of these findings, exploring the juxtaposition between a school culture that celebrates individual achievement and the culture of a dialogic classroom. For such classrooms, this research indicates that student commitment to dialogic interaction is encouraged where the ideas of all students are, as far as possible, acknowledged by the teacher and used in developing collective ideas.